Manufacturing of TiO2, Al2O3 and Y2O3 Ceramic Nanotubes for Application as Electrodes for Printable Electrochemical Sensors - Trandabat, Alexandru Florentin; Ciobanu, Romeo Cristian; Schreiner, Oliver Daniel; Aradoaei, Mihaela; Aradoaei, Sebastian Teodor (Crystals (Basel), 2024)
This paper describes the process to obtain ceramic nanotubes from titanium dioxide, alumina and yttrium oxide by a feasible, replicable and reliable technology, including three stages, starting from an electrospinning process of poly(methyl methacrylate) solutions. A minimum diameter of 0.3 μm was considered optimal for PMMA nanofibers in order to maintain the structural stability of covered fibers, which, after ceramic film deposition, leads to a fiber diameter of 0.5–0.6 μm. After a chemical and physical analysis of the stages of obtaining ceramic nanotubes, in all cases, uniform deposition of a ceramic film on PMMA fibers and, finally, a uniform structure of ceramic nanotubes were noted. The technological purpose was to use such nanotubes as ingredients in screen-printing inks for electrochemical sensors, because no study directly targeted the subject of ceramic nanotube applications for printed electronics to date. The printing technology was analyzed in terms of the ink deposition process, printed electrode roughness vs. type of ceramic nanotubes, derived inks, thermal curing of the electrodes and the conductivity of electrodes on different support (rigid and flexible) at different curing temperatures. The experimental inks containing ceramic nanotubes can be considered feasible for printed electronics, because they offer fast curing at low temperatures, reasonable conductivity vs. electrode length, good printability on both ceramic or plastic (flexible) supports and good adhesion to surface after curing.